REPRODUKSI NARASI TENTANG KEPAHLAWAN SOEHARTO: STUDI REPRESENTASI DI MUSEUM H.M. SOEHARTO - Ayu Dipta Kirana (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
The museum have the vision to become a media with the message and knowledge to share with a visitor. The vision of museum could be knowledge of museums representing national identity, culture, history, or biography of a public figures. The representation from one of a famous figure in Indonesia could we see in museum called Museum H.M. Soeharto. These articles aim to discover how the museum will work on Sang Bapak’s representation in the museum’s narration which are shown not only by a very lengthy text display but also on the attribute or object that scattered around in the museum’s yard. A whole object collection in museum will work based from the vision and aim of the museum. In the museum context, it called musealisation. It means that all the object collections are separated from their social context in real life then it enters the context of the museum so it will work based from the story or vision that made by what curator want and re-create the hero’s narration of Soeharto.